Existence and stability results for triple systems of fractional Sturm–Liouville–Langevin equations with cyclic boundary conditions - Chen, Gang; Bai, Zhanbing; Zhang, Wei (Nonlinear Analysis: Modelling and Control, 2026)
We investigate a triple system of fractional Sturm–Liouville–Langevin equations with cyclic antiperiodic boundary conditions. The fixed point theorem serves as a tool to establish the existence and uniqueness criteria for solutions. By applying the Banach contraction principle, we also obtain the Ulam–Hyers stability of the proposed system. Finally, examples are provided to illustrate main results.